Strategic survey 2019 the annual assessment of geopolitics (Strategic survey, 2019)
Strategic Survey analyses the events that shaped relations between major powers, region by region, in the last year, and identifies key themes for policymakers and analysts looking ahead to 2020. The 2019 edition features essays on 5G mobile network technology and geopolitics, The fate of the New START agreement, Afghanistan and regional politics after a US withdrawal, The Gulf States' competition in the Horn of Africa, Putin's Russia: consolidation and manoeuvre, Iran after Khamenei, Germany, 30 years after the fall of the Wall, Venezuela's crisis and the challenge of reconstruction.